EVALUASI LAYANAN BIMBINGAN DAN KONSELING DI SEKOLAH: PERSPEKTIF TEORETIS DAN PENDEKATAN STUDI LITERATUR - Hendrayani; Uman Suherman; Ibrahim Al Hakim (IKIP Siliwangi, 2026)
The evaluation of guidance and counseling services is a critical component in the management of school-based counseling programs to ensure alignment between planning, implementation, and outcomes relative to students' developmental needs. This study aims to examine the concept of guidance and counseling program evaluation as an integral part of a quality education system. Guidance and counseling services play a strategic role in facilitating students' personal, social, academic, and career development, thus requiring structured management, particularly through systematic evaluation. This study employed a qualitative approach using a literature review method, analyzing relevant books, regulations, and scientific articles related to guidance and counseling program evaluation. The findings indicate that guidance and counseling program evaluation is a systematic process for obtaining objective information regarding the effectiveness, efficiency, and impact of guidance and counseling services on students' development. The purposes of evaluation include assessing program implementation, measuring goal attainment, and providing feedback for program improvement. Evaluation serves a strategic function in decision-making, service quality enhancement, and the professional development of school counselors. This study further elaborates on the principles of evaluation, implementation procedures, evaluation approaches, methods, and data collection instruments including testing and non-testing techniques. Additionally, data sources and evaluation criteria are identified covering program formulation, service implementation, and outcomes achieved by students, teachers, schools, and the wider community. Overall, this study affirms that evaluation is an essential component in ensuring the quality of guidance and counseling services and supporting the optimal achievement of educational goals.